2001
DOI: 10.1159/000053851
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roxithromycin on Eotaxin-Primed Reactive Oxygen Species from Eosinophils

Abstract: Background: The CC chemokine eotaxin not only attracts eosinophils to inflamed sites but also promotes adhesion, degranulation and reactive oxygen species production of eosinophils. Reactive oxygen species released from eosinophils are believed to injure epithelial cells at inflamed sites, resulting in airway hyperresponsiveness. Roxithromycin has been reported to have antiasthmatic effects, although its mechanism of action is not thoroughly understood. Therefore, the effect of roxithromycin on eotaxin-primed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Inhibitory effects of erythromycin on eosinophil chemotactic cytokine release by lung fibroblasts may be one of the mechanisms of decreased airway hyperresponsiveness and the resulting amelioration of disease activity following therapy with that agent [30]. Macrolides may also protect epithelial cells at inflamed sites by inhibiting the release of reactive oxygen species from eosinophils [44].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitory effects of erythromycin on eosinophil chemotactic cytokine release by lung fibroblasts may be one of the mechanisms of decreased airway hyperresponsiveness and the resulting amelioration of disease activity following therapy with that agent [30]. Macrolides may also protect epithelial cells at inflamed sites by inhibiting the release of reactive oxygen species from eosinophils [44].…”
Section: Discussionmentioning
confidence: 99%
“…Their clinical effects in patients with dermatological diseases, such as psoriasis (Komine and Tamaki, 2000) and prurigo pigmentosa (Yazawa et al, 2001), were also reported. Recently, macrolides have been reported to be effective against bronchial asthma (Shoji et al, 1999), acting on eosinophils (Cui et al, 2001) and lymphocytes (Noma and Ogawa, 2003), (Noma et al, 2001). Roxithromycin (RXM) is one of the newly synthesized 14-membered ring macrolide antibiotics that is effective in treating acne vulgaris and bacterial infections (Bryskier, 1998).…”
mentioning
confidence: 99%
“…As for chemotaxis, no inhibition of ROS production was observed when neutrophils were stimulated by fMLP in the presence of ketotifen, suggesting a specific effect of this drug on eosinophils. Such an effect on the release of ROS by eosinophils activated with either PAF, IL‐5 or eotaxin has also been shown for some anti‐asthmatic drugs (38, 39). However, in his work, Ezeamuzie et al failed to show any significant effect of ketotifen on eosinophils activated with IL‐5 or PAF (38).…”
Section: Discussionmentioning
confidence: 81%